Executive Search Consultants’ Biases Against Women (or Men?) - Siegel, Rudolf; König, Cornelius J.; Zobel, Yannik (Frontiers in Psychology, 2020)
Women remain under-represented in leadership positions in many countries. Since executive search consultants (also known as headhunters) act as gatekeepers in the hiring process, headhunters’ biases might influence the female under-representation. There is preliminary evidence that suggests headhunters favor men but direct evidence is missing. Thus, this study directly tested this assumption using implicit and explicit measures (an implicit association test and a gender role attitudes survey), completed by 123 German executive search consultants. Although neither measure showed an anti-women bias (with the explicit measure being compared to a match sample from a representative survey using propensity score matching), the implicit association test showed an in-group bias (i.e., male headhunter had a stronger association of men and competence than of women and competence). The latter is worrisome because the majority of consultants in this business are men. Thus, organizations interested in more female managers need to carefully consider who they hire as their executive search consultants.